Paralisis Periodik Hipokalemia Menyerupai Sindom Guillain-Barre pada Wanita 36 Tahun : Laporan Kasus - Alidris, Rahardita; Tri Kuncoro, Prasetyo (PERDOSNI, 2024)
ABSTRACT Introduction: Hypokalaemic Periodic Paralysis (HPP) is a group of diseases manifested by acute flaccid paralysis and hypokalemia (<3.5 mmol/L). HPP is divided into hereditary and acquired causes. In addition to limb weakness, other complaints have been reported was sensory symptoms such as tingling and numbness in the limbs. These complaints can masquerading other diseases such as Guillain-Barre syndrome (GBS). Misdiagnosis between HPP and GBS may occur because the manifestations of HPP disease are similar in the early stages of GBS disease. Misdiagnosis can lead to wrong therapy and potentially life-threatening. Case Report: A 36-year-old woman was referred to the hospital with suspected of GBS. The patient complained of limb weakness since five days. Weakness begins in the legs and then into the hands. The complaint was accompanied by a feeling of soreness in the hands and feet about two weeks earlier and a tingling feeling in the mouth, hands and feet. The motoric strength 3/3/3, except in inferior dextra 2/2/2. Physiological reflexes +1 and reduced in muscle tone. Sensory examination is intact. There was a difference in potassium values ​​between before and after being referred (K+ 3.76 mmol/L vs 1.0 mmol/L). Significant clinical improvement after potassium correction therapy. Discussion: The manifestations of HPP that appear are not only related to the patient's motor abnormalities, but also sensory in the form of tingling and numbness. The mechanism by which the sensory dysfunction occurs is not well understood, but is suggested due to metabolic disturbances at the level of the dorsal root ganglia. So that the differential diagnosis of HPP can be raised in acute flaccid weakness accompanied by sensory symptoms. It may be considered to re-check electrolytes if risk factors and clinical symptoms lead to a clinical diagnosis of HPP. Keywords: Acute Flaccid Paralysis, Hypokalemic Periodic Paralysis, Guillain-Barre Syndrome